The relationship between diabetic patients' health beliefs and medication adherence among local ethnic groups in Kota samarahan and Sarikei - Cliffton Akoi, Pengarah (Universiti Malaysia Sarawak, (UNIMAS), 2011)
oiabetes mellitus (DM) is a chronic disease that results from defects in insulin secretion, insulin action, or both. The disease has both acute and long-term complications. DM cannot be treated. However, it can be controlled if patients adhere toward the prescribed treatment to prevent the complications of the disease. This cross-sectional study aims to examine the relationship between diabetic patients' health beliefs and medication adherence using the Health Belief Model (HBM) framewor0 Data collection was done by guided interview using pretested questionnaire, for which its internal reliability was tested using the Cronbach' s alpha. Information on the patients' socio-demographic and economic characteristics, medication adherence, characteristics of DM, perceptions on the disease, and health beliefs of 442 respondents was obtained. More than half of the respondents (6l.6%) were 51 years old and above, females (63 .8%), and were Malays (63.1%). Most of them (98.4%) were married, and 40.3% have no formal education. They were mostly self-employed or housewives (92.1 %). About 47.1% have family size of 4-5 persons, and more than half (61.7%) have monthly household income between RM500 to RM999. There was statistically significant difference (p<0.01) in terms of the respondents' age, gender, race, marital status, education level, occupation, family size, and monthly household income. The medication adherence rate was the lowest for follow-up treatment (24.2%). The adherence rates were also low for other treatment indicators such as taking amount of medication (3l.7%), frequency (38.9%), and duration of treatment (26%). The respondents' socio-demographic and economic aspects such as age, race, education level, occupation, household IIlcome, clinic distance, and transportation costs had statistically significant associations (p<0.05) with medication adherence. However, there was no statistically significant association (p>0.05) between gender, marital status, family size and medication adherence. Low level of education, poor income, clinic distance, and transportation costs have resulted in poor access to health care among the respondents. There was statistically significant association (p<0.05) between the respondents' perceptions about diabetic condition, diabetic control, seriousness of DM and its complications with medication adherence. The respondents aged 60 years and above have poorer adherence than others. Forgetfulness and complex treatment regimen were the main causes for non-adherence. Health beliefs about the seriousness of OM, benefits of treatment, barriers, and self-efficacy in taking medication have statistically significant association (p<0.05) with medication adherence. There was also statistically significant association (p<0.05) between cues to action in taking medication with medication adherence. The study has found that belief about the seriousness of OM was the strongest predictor of medication adherence. The other predictors were beliefs about the benefits of treatment and self-efficacy in taking medication. Medication adherence may be improved by modifying the relevant health beliefs about the disease and its management. Adherence may also be improved by addressing the problems of poor access to health care among the respondents.